The experimental and numerical studies on the effects of the operating conditions on the performance of breastshot waterwheel - Agato Agato; Deendarlianto Deendarlianto; Indarto Indarto; Alfeus Sunarso (Ain Shams Engineering Journal)
The aim of the present work was to investigate the effects of operating conditions on the flow behaviors and the generated power produced by breastshot waterwheels both experimentally and numerically. The experiments were carried out using a breastshot water wheel with the diameter of 500 mm, the width of 140 mm and the number of blades of 14. The wheel was installed on a channel with the weir head of 250 mm, the headrace length of 100 mm, and the water flow rate of 0.014 m3/sec. In the numerical simulation, the hydraulic channel was considered to be laterally symmetric, therefore only half of the section was taken into account. The simulation of free surface movement was calculated using the volume of fluid (VOF) method, and the static and rotating region interface was treated using the sliding mesh interface (SMI). The calculated torque and power, as well as the flow patterns ​​under various operating conditions are in a good agreement with those of the experiments. The visualization of the flow shows that the lower the rotational speed of the wheel, the greater the volume of water hitting the wheel blades, and the greater the torque produced by the water wheel. It was also confirmed that the periodical change of torque depends on the rotational speed and the number of wheel blades, and relates to the periodical change of the pressure on the blade surfaces. Furthermore, it is shown that the forward pressure that generates a positive torque mainly applies on a blade at a specific location. Under the decrease of rotational speed, the location of maximum forward pressure moves from the downstream blade to the upstream blade.